Acoustic erythrocytometer for mechanically probing cell viscoelasticity. Issue 11 (5th May 2020) - Link, A.; Franke, T.
Abstract : Novel microfluidic platform to determine the viscoelastic fingerprint of a red blood cell population using surface acoustic waves. Abstract : We demonstrate an acoustic device to mechanically probe a population of red blood cells at the single cell level. The device operates by exciting a surface acoustic wave in a microfluidic channel creating a stationary acoustic wave field of nodes and antinodes. Erythrocytes are attracted to the nodes and are deformed. Using a stepwise increasing and periodically oscillating acoustic field we study the static and dynamic deformation of individual red blood cells one by one. We quantify the deformation by the Taylor deformation index D and relaxation times τ 1 and τ 2 that reveal both the viscous and elastic properties of the cells. The precision of the measurement allows us to distinguish between individual cells in the suspension and provides a quantitative viscoelastic fingerprint of the blood sample at single cell resolution. The method overcomes limitations of other techniques that provide averaged values and has the potential for high-throughput.